2015
DOI: 10.1007/s00380-015-0696-7
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel significantly lowers the development of atherosclerosis in ApoE-deficient mice in vivo

Abstract: The anti-platelet drug clopidogrel has been shown to modulate adhesion molecule and cytokine expression, both playing an important role in the pathogenesis of atherosclerosis. The aim of this study was to investigate the impact of clopidogrel on the development and progression of atherosclerosis. ApoE(-/-) mice fed an atherogenic diet (cholesterol: 1 %) for 6 months received a daily dose of clopidogrel (1 mg/kg) by i.p. injection. Anti-platelet treatment was started immediately in one experimental group, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 37 publications
0
17
0
1
Order By: Relevance
“…In contrast, treatment of apoE−/− mice with the P2Y12 inhibitor clopidogrel bisulfate was associated with inconsistent results. While two groups found significant protection from atherosclerosis in clopidogrel-treated mice 27,28 , other groups could not reproduce these findings 29, 30 . Pharmacological inhibition is more likely to give variable results than a genetic approach.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In contrast, treatment of apoE−/− mice with the P2Y12 inhibitor clopidogrel bisulfate was associated with inconsistent results. While two groups found significant protection from atherosclerosis in clopidogrel-treated mice 27,28 , other groups could not reproduce these findings 29, 30 . Pharmacological inhibition is more likely to give variable results than a genetic approach.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, treatment of atherosclerotic patients with the P2Y12 inhibitor, clopidogrel, reduced the number of P-selectin-positive platelets and platelet-leukocyte aggregates in blood 25, 26 . In mice, an anti-atherogenic effect of clopidogrel was reported by some investigators 27, 28 , while others could not reproduce these results 29, 30 .…”
Section: Introductionmentioning
confidence: 93%
“…It has been reported that clopidogrel reduces CD4 + , CD8 + T cells, and macrophages infiltration in plaque, and the reason may be because of reduced adhesion molecules level such as intercellular adhesion molecule-1, E-selectin/P-selectin and cytokine level such as membrane cofactor protein-1 and platelet-derived growth factor. 26 In addition, cytokines such as platelet-derived growth factor and transforming growth factor-β released by activated platelet have been demonstrated to enhance VSMCs migration or proliferation in vitro. 27,28 Thus, platelet inhibition may indirectly inhibit VSMCs migration or proliferation during atherogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model of atherosclerosis by Apolipoprotein E (ApoE) gene knock-out, genetic P2Y 12 deletion was associated with reduced lesion area, increased fibrous content at the plaque site and decreased inflammatory cell infiltration [159]. Likewise, clopidogrel and ticagrelor limited the progression of late atherosclerotic lesion and promoted plaque stability in ApoE knockout mice [160][161][162][163]. Unfortunately, differential analysis of the role of platelet and non-platelet P2Y 12 receptors was not possible with these studies.…”
Section: Atherosclerosismentioning
confidence: 99%